Realization of state policy on the basis of projects for construction of industrial facilities in special economic zones - N. G. Verstina; D. Z. Iskandarov (Vestnik MGSU)
Introduction. The current economic conditions in the Russian Federation have significantly changed the priorities of state policy in the field of industrial development, which is expressed in the provision of an effective policy of spatial planning and creation of industrial facilities in regions where there are favourable conditions for this. One of the directions of the implementation of these policy priorities is the use of special economic zones (SEZ) with technological infrastructure for the implementation projects for the construction of industrial facilities on their territories. In this regard, it is relevant to develop a set of methods that contribute implementation of state policy in the field of industry, which will provide an objective assessment of prospects for the implementation of industrial construction projects in the SEZ, considering their advantages for the participants of the investment and construction process.Materials and methods. The initial materials of the study were the data of official statistics of the Russian Federation, characterizing investment processes in the industrial sector of the country. The methodological basis of the work was the provisions of theories of infographic modelling, functional systems, and statistical research methods — regression and correlation analysis, which are aimed at establishing the significance of indicators affecting the effectiveness of management and prospects for implementation of industrial construction projects in the SEZ.Results. As a result of the research, a set of indicators characterizing the prospects for implementation of industrial construction projects in the SEZ based on a comprehensive analysis of the project environment that surrounds it was formed. Analytical dependencies of the performance indicators of investment and construction organizations carrying out the construction of industrial facilities were established and formalized, allowing to determine the closeness of connection of these indicators and under conditions of variability of their values, which formed the basis of the developed set of evaluation methods.Conclusions. The developed approach to assessing the prospects for implementation of industrial construction projects in the SEZ allows expanding the information base for making managerial decisions when choosing locations for new industrial facilities, based on the specification of the conditions for implementation of project activities by its participants, established in the regions of the country. Improving of the state statistics data system in the proposed directions can expand the representativeness and range of analytics for decision-making.